Heterostructured SnO2-SnS2@C Embedded in Nitrogen-Doped Graphene as a Robust Anode Material for Lithium-Ion Batteries - Li, Hui; Zhang, Bao; Wang, Xu; Zhang, Jie; An, Tianhui; Ding, Zhiying; Yu, Wanjing; Tong, Hui (Frontiers in Chemistry, 2019)
Tin-based anode materials with high capacity attract wide attention of researchers and become a strong competitor for the next generation of lithium-ion battery anode materials. However, the poor electrical conductivity and severe volume expansion retard the commercialization of tin-based anode materials. Here, SnO2-SnS2@C nanoparticles with heterostructure embedded in a carbon matrix of nitrogen-doped graphene (SnO2-SnS2@C/NG) is ingeniously designed in this work. The composite was synthesized by a two-step method. Firstly, the SnO2@C/rGO with a nano-layer structure was synthesized by hydrothermal method as the precursor, and then the SnO2-SnS2@C/NG composite was obtained by further vulcanizing the above precursor. It should be noted that a carbon matrix with nitrogen-doped graphene can inhibit the volume expansion of SnO2-SnS2 nanoparticles and promote the transport of lithium ions during continuous cycling. Benefiting from the synergistic effect between nanoparticles and carbon matrix with nitrogen-doped graphene, the heterostructured SnO2-SnS2@C/NG further fundamentally confer improved structural stability and reaction kinetics for lithium storage. As expected, the SnO2-SnS2@C/NG composite exhibited high reversible capacity (1201.2 mA h g−1 at the current rate of 0.1 A g−1), superior rate capability and exceptional long-life stability (944.3 mAh g−1 after 950 cycles at the current rate of 1.0 A g−1). The results demonstrate that the SnO2-SnS2@C/NG composite is a highly competitive anode material for LIBs.